The acculturation effect and eyewitness memory reports among migrants - Anakwah, Nkansah (Legal and criminological psychology, 2020)
PURPOSE-When people migrate to new cultures, they adapt to their new culture while at the same time retaining the norms of their original culture. The phenomenon whereby migrants adapt to the cultural norms of a host culture has been referred to as acculturation. Using a mock witness paradigm, we examined the acculturation effect in the eyewitness memory reports of sub-Saharan African migrants in Western Europe.METHODS-We sampled sub-Saharan African migrants in Western Europe, as well as sub-Saharan Africans living in Africa as a control group (total N = 107). The mock witnesses were shown stimuli scenes of crimes in African and Western European settings and provided free and cued recall reports about what they had seen.RESULTS-Central details were reported more than contextual details by both groups of sub-Saharan Africans. Relative to the control group of sub-Saharan Africans living in Africa, sub-Saharan African migrants in Western Europe provided more correct central details in free recall. The longer migrants had resided in Western Europe, the less collectivistic they become. Migrants also provided more elaborate reports the longer their duration of residence in Western Europe.CONCLUSION-The findings of the current research suggest the new cultural environment of migrants impact their cultural norms, which may have implications for their eyewitness memory reports.